Identification of lactic acid bacteria from Meliponine honey and their antimicrobial activity against pathogenic bacteria - Nor Hazwani, Mohd Hasali; Amir Izzwan, Zamri; Mohd Nizam, Lani (2015)
Meliponine are known as non-stinger bees are popular for honey production and pollination activity in the fruit farms. They are native to the tropical and subtropical parts of the world such as Central and South America, Africa, Asia and Northern Australia. Although stingless bee honey (Kelulut honey) traditionally used as alternative medicine against bacterial infections, there are limited reports regarding their antimicrobial activity against pathogenic bacteria. This study reports the isolation and identification of lactic acid bacteria (LAB) from Meliponine honey produced in selected geographical locations in East Coast of Peninsular Malaysia and their antibacterial activity against pathogenic bacteria. The isolation of LAB from Meliponine honey conducted using MRS agar, MRS agar with 0.8% CaCO3, MRS agar with 10% glucose and M17 Agar. Colonies were purified with a streaking method followed by morphological and biochemical analysis using Gram staining, catalase text and oxidase test. These isolates were further characterized phenotypically using API 50 CHL. Molecular identification was based on nucleotide sequencing of 16S rRNA genes. Four isolates, LAB001-B, LAB002-C, LAB004-E and LAB005-F were identified as Lactobacillus brevis while one isolate (LAB003-D) was identified as Lactobacillus sp. The identified strains were further tested for antimicrobial activities against pathogenic bacteria such as Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Escherichia coli, Salmonella Typhimurium, Pseudomonas aeruginosa and Listeria monocytogenes by using welldiffusion method. All strains showed good inhibition activity only against S. epidermidis, P. aeruginosa and L. monocytogenes. The findings revealed that Meliponine honey has potential as antimicrobial activity for certain pathogenic bacteria that can be applied in food and pharmaceutical industries.